Partnering with Students to Connect Students - Ige, B. O.; Doyle, G.; Pienaar, L. (South African Journal of Higher Education, 2023)
Too often outreaches and interventions designed to support students transitioning to higher education, are developed by academics who may not have a full understanding of the complexity and diversity of their students’ realities. This disconnect explains why, in most cases, interventions are reactive instead of proactive. In this article, we draw on our experiences in terms of the design and implementation of a Student Resource Centre (SRC) to advocate for student and staff collaborative design. The student-run initiative works with students as partners to constitute and operationalise an innovative near-peer mentoring and support space. The mixed-methods study draws on social-cultural learning theory on student engagement and reflective practice tools. We explain how a student’s sense of belonging is central to their success, progression, and graduation. This article highlights the need to contextualise and personalise institutional support for students.